Why internet porn matters - Grebowicz, Margret (Stanford Briefs, 2013)
Acknowledgments; 1. The Critical Landscape of Pornography; 2. Why Speech Still Matters; 3. Democracy and the Information Society; 4. The Ecstasy of Community; 5. Privacy and Pleasure; 6. Foreclosure and Its Critics; 7. Inhuman Openings; 8. Pornography, Norms, and Sex Education; Notes; Bibliography